P452 Audit of MN-CMS Neonate Overview Clinical View Data at Day 2 Newborn Check. (June 2019) - Verrelli, Angela; Sweetman, Deirdre
Abstract : Introduction: Maternal and Newborn Clinical Management System (MN-CMS) is a new electronic medical record (EMR) that is used nationally in several maternity hospitals in Ireland. It was introduced to develop a paperless working environment and to facilitate access to patient information on a central system. In this audit, we aimed to evaluate the completeness of information entered in infants' EMR at birth and to assess which parameters are most frequently missing when the day 2 newborn check is performed. The aim was to identify which maternal and neonatal parameters are lacking and to increase awareness of this missing data. Method: For this audit, 100 infants' EMR were evaluated (50 public, 50 private patients) at two different time points to investigate if there was any difference in the recording rate from the Clinician View- Neonate Overview. Parameters included labour and birth information of the infants. All the data was analysed together and compared between the public and private patients. Results: Discussion: Results showed that though similar parameters were lacking in both groups, there was an improvement in recording noted in the second group (Date of Birth, Time of birth, Apgars, Gender, Estimated Gestational Age, Birthweight, Neonatal multiple gestation, Maternal age, Gravidity and Parity and Blood group). However, there are some areas that still require improvement and clarification as to when recording is needed or not. A follow-up audit is recommended to confirm that data recording training modules have been implemented and are successful.